Pengembangan Multimedia Pembelajaran Interaktif pada Mata Pelajaran Geografi Kelas XI SMA - Ningsih, Fitria; Novrianti, Novrianti; Eldarni, Eldarni; Hendri, Nofri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The development of this interactive learning Multimedia was made as an effort to utilize the use of Microsoft Office Power Point media, and can develop every year, and has an impact on students. This research aims to produce a learning multimedia product in Geography class XI of high school that is valid and practical. This type of research is R&D using the Four-D (4D) model consisting of define, design, develop, and disseminate. Product validation consists of media validation and material validation. The practicality test was carried out for students in grade XI of SMAN2 Sutera. Based on the research of the material validator, 4.81 is classified as